The Effect of Economic Growth and Unemployment on Profitability and Its Impact on the Stock Prices of Issuers Listed in the Lq45 Index for the 2017-2021 Period - Hari Widodo; Endang Etty Merawati; Syamsul Bahri (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This study aims to obtain empirical evidence of the effect of economic growth and unemployment on profitability and its impact on the stock price of issuers listed on the LQ45 Index. The sample used is the shares of issuers listed on the LQ45 Index on the Indonesia Stock Exchange (IDX). The research period used is from 2017 to 2020. The object in this study is the Issuer's Share Price which is listed on the LQ45 Index on the Indonesia Stock Exchange. The data used is secondary data. The reason is because issuers listed on this index tend to have high liquidity and market capitalization. Purposive sampling technique is a technique used in determining the sample and the total observations of the issuer's shares are 30 shares per year. The data analysis method used is SEM-PLS (Structural Equation Modeling-Partial Least Square) which is used as a hypothesis test technique. The results of this study indicate that economic growth has no effect on the stock price of issuers listed on the LQ45 Index, unemployment has no effect on profitability and stock prices of issuers listed on the LQ45 Index, economic growth has a significant effect on profitability and profitability as proxied by ROA and ROE has a significant effect. to the share price of issuers listed on the LQ45 Index. Profitability as an intervening variable has the effect of variable economic growth on stock prices. and Profitability as an intervening variable does not affect the unemployment variable on stock prices.